Prevalencia y factores de riesgo asociados a patología maligna y pre maligna de cuello de útero en el Centro Médico Loja periodo 2011-2015. - Zapata Tapia, Evelyn Gabriela (2017)
Cervical cancer is one of the most common pathologies in women, it is the second most common cancer in the world and the prevalence of lesions is high despite screening tests for diagnosis. The purpose of this research was to identify the prevalence per age group and risk factors associated with malignant and premalignant cervical pathology and their relationship between them at the Loja Medical Center during the period 2011-2015. Data was obtained by means of a review of clinical records and colposcopy records of the women who visited the center during this period. Out of 1536 women, 341 cases met the inclusion criteria for malignant lesions or cervical premalignant lesions. Finally the filling of the data collection sheets for the nominated risk factors was carried out. A total of 341 cases were established, of which 323 corresponded to premalignant lesions, 255 low-grade LIE lesions, 68 high-grade LIE lesions, and 18 cases of malignant lesions. The most prevalent age was 25 to 34 years and 45 to 54 years for pre-malignant and malignant lesions, respectively. The most prevalent risk factor was the presence of HPV which was found in 246 cases. Key words: Prevalence, risk factors, cervical cancer, premalignant lesions